(1→6)- and (1→3)(1→6)-β-glucans from Lasiodiplodia theobromae MMBJ: Structural characterization and pro-inflammatory activity. (20th November 2015) - Oliveira, Kassandra S.M.; Di Bastiani, Mirela; Cordeiro, Lucimara M.C.; Costa, Mírian F.; Toledo, Karina A.; Iacomini, Marcello; Babosa, Aneli M.; Dekker, Robert F.H.; Nascimento, Valéria M.G.
Abstract: The chemical composition and structural characterization of exopolysaccharides from the fungus Lasiodiplodia theobromae MMBJ are described, and the immunomodulatory activity of a purified β-glucan was evaluated. L. theobromae MMBJ produced three different β-glucans. One, fraction PEPS, was a branched (1→3)(1→6)-β-glucan and was insoluble in cold water. The other two, fractions SEPS-005R and SEPS-10E, were characterized as linear (1→6)-β-glucans with molar mass of 1.8 × 10 6  Da and 7.0 × 10 3  Da, respectively. From a total of 2.2 g/L of EPS produced by L. theobromae through submerged fermentation, 1.5 g/L (67%) was of the branched (1→3)(1→6)-β-glucan, while 25% (w/w) were linear (1→6)-β-glucans. Tests conducted with macrophages showed that the high molar mass (1→6)-β-glucan fraction (SEPS-005R) induced a pro-inflammatory response pattern.